Glycerine preservation of foliage for value-addition - Singh, Babita; Jain, Ritu; Sindhu, S S; Yadav, Harendra; Kumar, Raman (Indian Horticulture, 2019)
Glycerinization is the term used in the ornamental cut flower and foliage processing industry to describe treating fresh plant material with a hygroscopic (waterattracting) chemical. The objective is to retain the suppleness of plant material. Plant material preserved with glycerine has rich colour and texture that makes it ideal for fall and winter crafts. Glycerine treatment is usually used for foliage, but baby’s breath (Gypsophila elegans) and the flower heads on grasses can also be preserved with glycerine. The transformation is amazing to watch as deep green leaves take on shades of orange, yellow, red and bronze, resulting in a multicolor display. Thus, attractive plant material, sometimes with several colours on a single plant and durable stems and flowers that last for years develop.